The Evolution of Global Recruitment Practices: A Bibliometric Review - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study aims to examine the evolution of global recruitment practices by mapping the intellectual structure, thematic development, and collaboration patterns within the academic literature. A bibliometric approach was employed using publication data retrieved from the Scopus database, covering peer-reviewed articles related to global recruitment, international recruitment, and cross-border labor hiring. The analysis utilized VOSviewer to conduct keyword co-occurrence, overlay and density visualization, co-authorship, institutional collaboration, and country collaboration analyses. The results reveal that early research on global recruitment predominantly focused on employment relations, international labor migration, and legal–institutional frameworks, particularly emphasizing the role of international organizations and labor governance. Over time, recruitment emerged as a central analytical concept connecting governance perspectives with ethical and risk-oriented concerns. Recent research trends demonstrate a strong shift toward issues of fair recruitment, forced labor, sexual exploitation, and the use of administrative data for monitoring and accountability. The collaboration analysis shows that knowledge production is concentrated among a relatively small network of authors and institutions, mainly from developed countries, with limited cross-national collaboration. Overall, this study provides a comprehensive overview of the development and current direction of global recruitment research and highlights opportunities for future studies focusing on ethical governance, data-driven oversight, and more inclusive international collaboration.